Fingerprint Biometric for Identity Management - Manivannan, Nadarajah; Tigli, Celalettin; Noor, Azad; Memon, Shahzad (International Journal of Industrial Engineering and Management, 2011)
In this paper a study of fingerprint biometric for Identity management is presented. Basic stages of automatic fingerprint systems are explained and a comparison study among three commercially available automatic fingerprint recognition systems is also presented. This study suggests that automatic fingerprint recognition systems performs reliably well as far as recognition is concerned, however there is a number of areas, such as liveness detection and unsupervised recognition, need to be tackled for high security applications, such as border control and anti-terror activities. Article history: Received (02 March 2011); Revised (04 May 2011); Accepted (17 May 2011)